MATHEMATICAL FORMULAE AND THEIR INTERPRETATIONS. - Galitzer, Philip (The Accounting Review, 1947)
In actual practice, is there such a thing as interpreting mathematical formulae with precision? The writer thinks not. The magnitude and complexities of the problems involved in many given situations give rise to interpretations requiring the aid of the courts. Untold factors must be considered before arriving at a decision. The law governing a stated situation must be determined upon the facts and circumstances of the particular case. That there has been constant and recurring litigation with respect to construction and interpretation of mathematical formulae is best attested by legions of cases officially and unofficially reported. The various cases discussed and set forth below merely touch the fringe in the gamut of mathematical formulae and their interpretations. Although the use of care and precision in describing mathematical formulae is essential if litigation is to be minimized or avoided, nevertheless even apparently simple formulae are inherently fraught with dangers that may involve expense and adverse rulings. Too often formulae are inartistically drafted and cluttered with barnacles of if's, and's, and but's.